Sheet for structure
By using polymer compositions with high and low glass transition temperatures and multi-layered sheets, the problem of insufficient weather resistance and compliance in roof repair and reinforcement in the prior art is solved, and effective on complex roof structures is achieved Leak protection and adaptability.
Patent Information
- Application Number
- CN202380046823.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-24
- Filing Date
- 2023-07-25
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing structural protective sheets have shortcomings in weather resistance and compliance, especially in the repair and reinforcement of roofs, it is difficult to effectively prevent rain leakage and adapt to complex roof structures.
The polymer composition of a first base material polymer with a high glass transition temperature and a second base material polymer with a low glass transition temperature is used to combine the multi-layer structure of the adhesive layer, the functional layer and the intermediate layer to ensure that The sheet has excellent weather resistance and compliance when attached to the structure.
The weather resistance and compliance of the sheet in high temperature and cold environments can be achieved, which can effectively prevent roof leakage and adapt to complex roof structures, improving the effect and operability of repair and reinforcement.
Smart Images

Figure CN119317539A_ABST
Abstract
Description
Technical Field
[0001] This specification discloses a sheet material to be used in a state of being attached to a structure. Background Art
[0002] When exposed to wind and rain for a long period of time, a roof covered with artificial slate tiles deteriorates. There is a concern about leaks on the roof that has deteriorated. For the purpose of preventing roof leaks, paint is applied to artificial slate tiles. However, in the case of a roof covered with artificial slate tiles that has significantly deteriorated, applying paint cannot prevent roof leaks in some cases.
[0003] WO 2021 / 010456 discloses a structural protection sheet. The sheet has a polymer segment layer and a resin layer. When the sheet is attached to a roof, it can suppress roof leakage.
[0004] [Citation List] [Patent Document] [Patent Document 1] WO 2021 / 010456. Summary of the invention
[0005] [Technical issues] The sheet for protecting a structure is required to have excellent weather resistance (heat resistance). The sheet for protecting a structure is further required to have good conformability to the roof. It is desirable that the sheet has both weather resistance and conformability.
[0006] In the repair of roofs not covered with artificial slate tiles, the sheet is also required to have both weather resistance and compliance. In the repair or reinforcement of structures other than roofs, the sheet is also required to have both weather resistance and compliance.
[0007] The applicants of the present invention aim to provide a sheet material for structures having excellent weather resistance and conformability.
[0008] [Solution to the problem] The sheet material for a structure disclosed in this specification has an adhesive layer and a functional layer whose material is a polymer composition. The polymer composition contains a first base material polymer and a second base material polymer. The first base material polymer has a first glass transition temperature T1. The second base material polymer has a second glass transition temperature T2. The second glass transition temperature T2 is lower than the first glass transition temperature T1.
[0009] [Advantageous Effects of the Invention] In the sheet for structures, a resin having a high glass transition temperature can contribute to weather resistance. In addition, in the sheet, a resin having a low glass transition temperature can contribute to compliance. The sheet for structures is excellent in both weather resistance and compliance. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 is a perspective view showing a portion of a sheet for a structure according to one embodiment; Figure 2 is along Figure 1 A cross-sectional view taken along the midline II-II; Figure 3 It is shown by Figure 2 An enlarged view of the portion indicated by reference numeral III in FIG. Figure 4 It is shown Figure 1 A cross-sectional view of the sheet material used for the structure together with the roof; Figure 5 It is shown by Figure 4 An enlarged view of the portion indicated by reference numeral V in FIG. Figure 6 It is shown by Figure 4 An enlarged view of the portion indicated by reference numeral VI in FIG. Figure 7 It is shown that the Figure 1 An enlarged plan view of a portion of a reinforcement in a sheet for a structure; Figure 8 is a cross-sectional view showing a portion of a sheet for a structure according to another embodiment. DETAILED DESCRIPTION
[0011] Hereinafter, preferred embodiments will be described in detail with reference to the accompanying drawings as appropriate.
[0012] [Example 1] [Layer structure] Figures 1 to 3 A sheet 2 is shown for use in a structure. Figure 1 In FIG. 1 , arrow X indicates the width direction of the sheet 2, arrow Y indicates the length direction of the sheet 2, and arrow Z indicates the thickness direction of the sheet 2. The planar shape of the sheet 2 is generally rectangular. Figure 3 As is clear from the figure, the sheet 2 has a functional layer 4, an intermediate layer 6, an adhesive layer 8 and a reinforcement 10. The reinforcement 10 is in a state of being buried in the intermediate layer 6. The materials of each layer, etc. will be described in detail below. The sheet 2 is attached to the structure. The sheet 2 may have a release paper or a release film. The release paper and the release film are laminated on the adhesive layer 8.
[0013] [Roof repair] A typical use of the sheet material 2 for structures is the repair of roofs. Figures 4 to 6 A repaired roof 12 is shown. In these drawings, two sheets 2 (a first sheet 2a and a second sheet 2b) are shown together with the roof 12. The specifications of the second sheet 2b are the same as those of the first sheet 2a. Examples of the roof 12 include an artificial slate roof, a tile roof, a steel roof (including a folded plate roof), a copper roof, a galvanized iron roof, a concrete roof, and the like.
[0014] exist Figure 4 In the embodiment, the position of the lower edge 14a of the first sheet 2a is substantially consistent with the position of the lower edge 16 of the roof 12. The first sheet 2a is attached to the roof 12 as a whole. Figure 5 As shown in FIG. 1 , the roof 12 has a step 18. The first sheet 2a is bent near the step 18. The bending makes the first sheet 2a conform to the step 18.
[0015] like Figure 6 As shown, the second sheet 2b overlaps the upper edge 20a of the first sheet 2a near its lower edge 14b. This overlap forms a seam 22. In the second sheet 2b, the portion other than the seam 22 is attached to the roof 12. The upper edge 20a of the first sheet 2a forms a step 24 between the first sheet 2a and the roof 12. The second sheet 2b is bent near the step 24. This bending allows the second sheet 2b to conform to the step 24.
[0016] [Primer layer] The sheet 2 for a structure is usually pasted to the roof 12 (with a primer layer in between). In this specification, the case where the sheet 2 is pasted to the roof 12 through the primer layer or the like will also be referred to as "the sheet is pasted to the roof". Figure 5 and 6 In the figure, the primer layer is not shown.
[0017] The material of the primer layer is preferably a curable resin composition. As curable resins, thermosetting resins and photocurable resins are exemplified. Preferred thermosetting resins are epoxy compounds. As epoxy compounds, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, o-cresol novolac type epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, diglycidyl ethers of phenols and diglycidyl ethers of alcohols are exemplified. As curing agents for epoxy compounds, polyfunctional phenols, amines, polyamines, thiols, imidazoles, acid anhydrides and phosphorus-containing compounds are exemplified.
[0018] [Young's modulus of sheet] The Young's modulus of the sheet 2 for the structure is preferably 20 MPa or more and 300 MPa or less. When tension is applied to the sheet 2 having a Young's modulus of 20 MPa or more, permanent deformation and breakage are unlikely to occur. The sheet 2 has excellent operability. From this point of view, the Young's modulus is more preferably 30 MPa or more and particularly preferably 40 MPa or more. The sheet 2 having a Young's modulus of 300 MPa or less has excellent compliance. From this point of view, the Young's modulus is preferably 280 MPa or less and particularly preferably 260 MPa or less. The Young's modulus is measured according to the definition of "JIS K 7161". As an apparatus suitable for the measurement, the "Precision Universal Testing Machine AGXTM-V" manufactured by SHIMADZUCORPORATION is exemplified.
[0019] [Water vapor transmission rate of sheet] The water vapor transmission rate of the sheet material 2 for structures is preferably 10 g / m 2 · day or more. When the sheet 2 has been attached to a structure, moisture contained in the structure or moisture present between the structure and the sheet 2 can be discharged through the sheet 2. The sheet 2 can inhibit corrosion of metal in the structure. The sheet 2 is also suitable for structures containing moisture (for example, structures with insufficiently dried concrete). The sheet 2 is also suitable for construction during rainy days. From these viewpoints, the water vapor transmission rate is more preferably 20 g / m 2 day or more and particularly preferably 25 g / m 2 · days or more. The water vapor transmission rate is preferably 50 g / m 2 · days or less. The water vapor transmission rate is measured according to the definition of "JIS Z 0208".
[0020] [Functional layer] As from Figure 3 As is clear from the above, in the embodiment of the present invention, the functional layer 4 is located at the top. In other words, when the sheet 2 has been attached to the structure, the position of the functional layer 4 is farthest from the structure in the thickness direction Z (see Figure 1 ). The functional layer 4 contributes to the desired function of the sheet 2. As the function, weather resistance, abrasion resistance, chemical resistance, water impermeability, moisture impermeability and moisture permeability are exemplified. Typical weather resistance is heat resistance and light resistance. The functional layer 4 can contribute to one or more functions.
[0021] The preferred material of the functional layer 4 is a polymer composition. The functional layer 4 is usually flexible. The sheet 2 for a structure having the functional layer 4 can conform to the unevenness of the substrate. The polymer composition contains a base material polymer. Synthetic resin, synthetic rubber and natural rubber can be included in the composition as the base material polymer. The functional layer 4 whose base material polymer is a synthetic resin is also referred to as a "resin layer".
[0022] In the case where light resistance is desired in the functional layer 4, a base material polymer that is less likely to deteriorate due to ultraviolet rays is preferred. Specifically, a polymer having a stronger binding energy than ultraviolet rays (410 KJ / mol) is preferred. As polymers that can contribute to the light resistance of the functional layer 4 and the flexibility of the sheet 2, acrylic resins, acrylic urethane resins, acrylic silicone resins, fluororesins, soft epoxy resins, and polybutadiene are exemplified.
[0023] From the viewpoint of light resistance, a resin particularly suitable for the base material polymer of the functional layer 4 is an acrylic silicone resin. Acrylic silicone resin has a siloxane bond. Acrylic silicone resin also has excellent heat resistance and cold resistance. Specific examples of compositions containing acrylic silicone resins include "COOL LIFE SP BLACK (CB1) P5-0" from Dainichiseika Color & Chemicals Mfg. Co., Ltd., "BELLEARTH ELASTIC BLACK" from Fujikura Kasei Co., Ltd., "ARONBULLCOAT T-1000" from Toagosei Co., Ltd., and "ACRYSET EMN325E" and "UWR EF-008" from NIPPON SHOKUBAI CO., LTD.
[0024] [Glass transition temperature of base material polymer] In an embodiment of the present invention, the polymer composition contains a first base material polymer and a second base material polymer. The glass transition temperature (Tg) of the second base material polymer is different from the glass transition temperature (Tg) of the first base material polymer. In this specification, the glass transition temperature of the first base material polymer will be referred to as the first glass transition temperature T1, and the glass transition temperature of the second base material polymer will be referred to as the second glass transition temperature T2. The second glass transition temperature T2 is lower than the first glass transition temperature T1.
[0025] According to the knowledge obtained by the inventors of the present invention, a polymer having a high glass transition temperature (Tg) can contribute to the weather resistance of the sheet 2 for a structure. The polymer can particularly contribute to the heat resistance of the sheet 2. From this viewpoint, the first glass transition temperature T1 is preferably 25°C or higher, more preferably 27°C or higher, and particularly preferably 29°C or higher.
[0026] According to the knowledge acquired by the inventors of the present invention, a polymer having a low glass transition temperature (Tg) can contribute to the conformability of the sheet 2 for use in a structure. The polymer can particularly contribute to the conformability when the sheet 2 is attached to a roof 12 or the like in a cold environment. Figure 5 When the step difference 18 shown in FIG. 1 is shown, the sheet 2 is unlikely to crack. Figure 6 The sheet 2 is also less likely to crack when the step difference 24 shown in FIG. 2 is less than 24. From the viewpoint of compliance, the second glass transition temperature T2 is preferably -10°C or lower, more preferably -13°C or lower, and particularly preferably -15°C or lower.
[0027] The sheet material 2 for a structure has both heat resistance, which is an advantage of the first base material polymer, and compliance, which is an advantage of the second base material polymer. From the viewpoint of heat resistance and compliance, the difference (T1 - T2) between the first glass transition temperature T1 and the second glass transition temperature T2 is preferably 30°C or more, more preferably 35°C or more, and particularly preferably 40°C or more.
[0028] The polymer composition may contain different base material polymers. The glass transition temperature (Tg) of the different base material polymers is different from the first glass transition temperature T1 and also different from the second glass transition temperature T2.
[0029] The glass transition temperature (Tg) is calculated based on the storage modulus measured with a dynamic viscoelasticity measuring device. As an apparatus suitable for the measurement, "DMAQ850Rheometer DHR-2" from TA Instruments Japan Inc. is exemplified. A test piece cut out from the functional layer 4 is used for the measurement. The measurement conditions are described below: Dimensions of the test piece: 40 mm × 5 mm Heating rate: 5°C / min Measuring range: -20°C to 100°C Frequency: 1 Hz Strain: - 0.1%.
[0030] [Polymer Combination] The system of the second base material polymer is preferably the same as the system of the first base material polymer. As a preferred combination of the first base material polymer and the second base material polymer, the following items are exemplified: (1) a combination of an acrylic resin having a high glass transition temperature and an acrylic resin having a low glass transition temperature, (2) a combination of an acrylic urethane resin having a high glass transition temperature and an acrylic urethane resin having a low glass transition temperature, and (3) A combination of an acrylic silicone resin having a high glass transition temperature and an acrylic silicone resin having a low glass transition temperature.
[0031] The mass ratio of the first base material polymer to the second base material polymer in the polymer composition is preferably 30 / 70 or more and 80 / 20 or less. The sheet material 2 for a structure having a mass ratio of 30 / 70 has excellent heat resistance. From this point of view, the mass ratio is more preferably 40 / 60 or more and particularly preferably 45 / 55 or more. The sheet material 2 for a structure having a mass ratio of 80 / 20 or less has excellent compliance. From this point of view, the mass ratio is more preferably 70 / 30 or less and particularly preferably 65 / 35 or less.
[0032] [Glass transition temperature of polymer composition] The polymer composition contains a plurality of base material polymers, and therefore the polymer composition has a plurality of glass transition temperatures (Tg). In this specification, the highest glass transition temperature in the polymer composition will be referred to as the upper glass transition temperature TU, and the lowest glass transition temperature in the polymer composition will be referred to as the lower glass transition temperature TL. From the viewpoint of heat resistance, the upper glass transition temperature TU is preferably 15°C or higher, more preferably 20°C or higher and particularly preferably 25°C or higher. The upper glass transition temperature TU is preferably 30°C or lower. From the viewpoint of compliance, the lower glass transition temperature TL is preferably 0°C or lower, more preferably -5°C or lower and particularly preferably -8°C or lower. The lower glass transition temperature TL is preferably -15°C or higher.
[0033] From the viewpoint of heat resistance and compliance of the functional layer 4, the difference (TU - TL) between the upper limit glass transition temperature TU and the lower limit glass transition temperature TL is preferably 20°C or more, more preferably 25°C or more, and particularly preferably 30°C or more. From the viewpoint of uniformity of the functional layer 4, the difference (T1 - T2) is preferably 50°C or less.
[0034] [Characteristics of functional layer] In an environment at a temperature of 5°C, the elongation at break of the functional layer 4 is preferably 10% or more and 175% or less. The sheet 2 for a structure in which the elongation at break of the functional layer 4 is 10% or more has excellent compliance. From this point of view, the elongation at break is more preferably 30% or more and more preferably 50% or more. The sheet 2 for a structure in which the elongation at break of the functional layer 4 is 175% or less has excellent durability. From this point of view, the elongation at break is more preferably 155% or less and more preferably 140% or less.
[0035] In an environment where the temperature is 80°C, the elongation at break of the functional layer 4 is preferably 250% or more. The elongation at break at this temperature is related to the heat resistance of the sheet 2 for a structure. From the viewpoint of heat resistance, the elongation at break is more preferably 300% or more and particularly preferably 350% or more.
[0036] The elongation at break is measured according to the definition of "JIS K 7161". As an apparatus suitable for the measurement, "Precision Universal Testing Machine AGXTM-V" manufactured by SHIMADZU CORPORATION is exemplified. In the test, a constant temperature apparatus is used. As a constant temperature apparatus suitable for the test, "Constant Temperature and Humidity Chamber THC1" manufactured by SHIMADZU CORPORATION is exemplified. The measurement conditions are described below: Test piece shape: Flat plate The size of the test piece: 15 mm × 100 mm Distance between chucks: 20 mm Tensile speed: 200 mm / min.
[0037] In the case where the functional layer 4 is desired to be water-impermeable and moisture-permeable, the water vapor permeability of the functional layer 4 is preferably 10 g / m 2 · days or more and 50 g / m 2 · days or less. The water vapor transmission rate is measured according to the definition of "JIS Z 0208".
[0038] As required, the polymer composition for the functional layer 4 may contain additives such as pigments, fillers, reinforcing materials or antifouling materials. The functional layer 4 containing pigments has excellent designability. Organic pigments and inorganic pigments may be contained in the polymer composition. As fillers, metal oxide particles of silicon dioxide, aluminum oxide, titanium dioxide, etc. are exemplified. As reinforcing materials, cellulose nanofibers are exemplified. Depending on the function, the content ratio of each additive is adjusted.
[0039] Figure 3 The arrow t1 in indicates the thickness of the functional layer 4. From the functional point of view, the thickness t1 is preferably 10 μm or more, more preferably 30 μm or more and particularly preferably 50 μm or more. From the compliance, productivity and lightweight point of view of the sheet 2, the thickness t1 is preferably 500 μm or less, more preferably 300 μm or less and particularly preferably 150 μm or less. The distribution of the thickness t1 is preferably within the range of ± 50 μm. The sheet 2 for the structure may have two or more functional layers 4.
[0040] [Middle layer] The intermediate layer 6 contributes to the rigidity of the sheet 2, etc. A preferred material for the intermediate layer 6 is a composite material of a polymer and a filler. As polymers in the composite material, acrylic resins, acrylic silicone resins, fluororesins, silicone resins, epoxy resins, ethylene-vinyl acetate copolymers, and styrene-butadiene copolymers are exemplified. As fillers in the composite material, cement, silica, alumina, titanium oxide, calcium carbonate, and carbon black are exemplified. A preferred composite material is polymer cement. The polymer cement contains a polymer and cement. A typical polymer is an acrylic resin. As cement, Portland cement, alumina cement, and mixtures thereof are exemplified. Portland cement is preferred. The intermediate layer 6 whose material is polymer cement is also referred to as a "polymer cement cured layer".
[0041] In the case where the intermediate layer 6 contains a polymer and cement, the mass ratio of the polymer in the solid content of the intermediate layer 6 is preferably 10% or more and 40% or less. The intermediate layer 6 in which the ratio is 10% or more has excellent adhesion to other layers (functional layer 4 or adhesive layer 8). From this viewpoint, the ratio is more preferably 15% or more and particularly preferably 20% or more. The intermediate layer 6 in which the ratio is 40% or less can contain a sufficient amount of cement. From this viewpoint, the ratio is more preferably 35% or less and particularly preferably 30% or less.
[0042] In the case where the intermediate layer 6 contains a polymer and cement, the mass ratio of cement in the solid content of the intermediate layer 6 is preferably 20% or more and 70% or less. In the sheet 2 for a structure having the intermediate layer 6 in which the ratio is 20% or more, high tensile strength and small elongation can be achieved. The sheet 2 has excellent workability. From this viewpoint, the ratio is more preferably 30% or more and particularly preferably 35% or more. The intermediate layer 6 in which the ratio is 70% or less can contain a sufficient amount of polymer. From this viewpoint, the ratio is more preferably 60% or less and particularly preferably 55% or less.
[0043] The intermediate layer 6 containing polymer and cement has excellent water vapor permeability. Even when a structure is covered with the sheet 2 having the intermediate layer 6, the metal in the structure is less likely to corrode. The water vapor permeability of the intermediate layer 6 is preferably 20 g / m 2 · days or more and 60 g / m 2 · days or less. The water vapor transmission rate is measured according to the definition of "JIS Z 0208".
[0044] The intermediate layer 6 can be formed by a liquid mixture obtained from a composition containing a polymer and a composition containing cement. The preferred composition containing a polymer is an acrylic emulsion. The acrylic emulsion can be obtained by emulsion polymerization of monomers. Emulsion polymerization can be carried out with an emulsifier. Polymerization can be carried out in water containing a surfactant. Typical monomers are acrylates or methacrylates. The content of the monomer component in the acrylic emulsion is 20% to 100% by mass.
[0045] Specific examples of the composition containing a polymer include a trade name “SPRING COAT BRUSH MIXTURE” from KIKUSUI Chemical Industries Co., Ltd. and a trade name “ARONBULLCOAT A450 BASE” from Toagosei Co., Ltd. Specific examples of the composition containing cement include a trade name “SPRING COAT BRUSH POWDER” from KIKUSUI Chemical Industries Co., Ltd. and a trade name “ARONBULLCOAT A450 SETTER” from Toagosei Co., Ltd.
[0046] Figure 3 The arrow t2 in FIG. 1 indicates the thickness of the intermediate layer 6. In the embodiment of the present invention, as described above, the reinforcement 10 is in a state of being buried in the intermediate layer 6. Therefore, the thickness t2 is measured, including the reinforcement 10. From the viewpoint of the operability of the sheet 2, the thickness t2 is preferably 100 μm or more, more preferably 300 μm or more, and particularly preferably 500 μm or more. From the viewpoint of the compliance, productivity, and lightweight of the sheet 2, the thickness t2 is preferably 1500 μm or less, more preferably 1000 μm or less, and particularly preferably 700 μm or less. The distribution of the thickness t2 is preferably within the range of ± 100 μm.
[0047] The material of the intermediate layer 6 may be a resin composition or a rubber composition. The sheet 2 for a structure may have two or more intermediate layers 6. The sheet 2 for a structure may have two intermediate layers 6 whose materials are different from each other. The sheet 2 for a structure may have a layer configuration in which the intermediate layer 6 is not included.
[0048] From the viewpoint of adhesion of the intermediate layer 6 to the functional layer 4 , the base material polymer of the intermediate layer 6 is preferably the same as the base material polymer of the functional layer 4 .
[0049] [Adhesive layer] The adhesive layer 8 (or bonding adhesive layer) is in contact with the substrate. The sheet 2 is attached to the structure by the adhesive force of the adhesive layer 8. The adhesive layer 8 enables a 0.5 N / mm 2 or higher adhesion.
[0050] The preferred material of the adhesive layer 8 is an adhesive composition containing a polymer as a base material. As polymers suitable for the adhesive composition, acrylic resins, silicones, polyurethanes, polyesters, natural rubbers and synthetic rubbers are exemplified. The polymer particularly preferably used as the base material is an acrylic resin. Specific examples of the adhesive composition include the trade names "ORIBAIN BPS 6574", "ORIBAIN BPS6554" and "ORIBAIN BPS 5565K" from TOYOCHEM CO., LTD.
[0051] The adhesive composition may contain a curing agent. In the case where the base material is an acrylic resin, a preferred curing agent is an isocyanate curing agent. The ratio of the isocyanate curing agent to 100 parts by mass of the acrylic resin is preferably 1.0 parts by mass or more, more preferably 2.0 parts by mass or more, and particularly preferably 2.5 parts by mass or more. The ratio is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and particularly preferably 7 parts by mass or less.
[0052] The adhesive composition may contain a tackifier. As tackifiers, rosin-based tackifiers, terpene-based tackifiers, petroleum resin-based tackifiers, and phenolic resin-based tackifiers are exemplified. The ratio of the tackifier to 100 parts by mass of the base material polymer is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, and particularly preferably 1.5 parts by mass or more. The ratio is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, and particularly preferably 7 parts by mass or less. Specific examples of tackifiers include trade names "ESTER GUM H", "ESTER GUM AA-V", and "ESTER GUM105" from ARAKAWA CHEMICAL INDUSTRIES, LTD.
[0053] Figure 3 The arrow t3 in FIG. indicates the thickness of the adhesive layer 8. From the viewpoint of adhesion, the thickness t3 is preferably 20 μm or more, more preferably 40 μm or more, and particularly preferably 50 μm or more. From the viewpoint of productivity, lightness, and operability of the sheet 2, the thickness t3 is preferably 500 μm or less, more preferably 200 μm or less, and particularly preferably 150 μm or less. The amount of the adhesive layer 8 is preferably 20 g / m 2 or larger and 250 g / m 2 The sheet material 2 for a structure may have two or more adhesive layers 8 .
[0054] [Reinforcement] The reinforcement 10 can give the sheet 2 used for the structure an appropriate Young's modulus. The reinforcement 10 can contribute to the large tensile strength of the sheet 2. In addition, the reinforcement 10 can contribute to the small elongation of the sheet 2. The sheet 2 including the reinforcement 10 has excellent operability. As described above, the reinforcement 10 is in a state of being buried in the intermediate layer 6. The reinforcement 10 can be in a state of being buried in the functional layer 4. The reinforcement 10 can be in a state of being buried in the adhesive layer 8. The reinforcement 10 can also be located between the functional layer 4 and the intermediate layer 6. The reinforcement 10 can also be located between the intermediate layer 6 and the adhesive layer 8. In this specification, the reinforcement 10 means an object that can give the sheet 2 a large tensile strength compared to an imaginary sheet having the same layer structure as the sheet 2 but not including the reinforcement 10.
[0055] [Tensile strength and elongation of reinforcement] The tensile strength of the reinforcement 10 is preferably 5.0 MPa or higher. The sheet 2 in which the tensile strength of the reinforcement 10 is 5.0 MPa or higher is less likely to break even when a tensile force is applied thereto. The sheet 2 has excellent operability. From this point of view, the tensile strength is more preferably 5.5 MPa or higher and particularly preferably 6.0 MPa or higher. From the perspective of the compliance of the sheet 2, the tensile strength of the reinforcement 10 is preferably 15.0 MPa or lower, more preferably 10.0 MPa or lower and particularly preferably 7.0 MPa or lower.
[0056] The elongation at break of the reinforcement 10 is preferably 15.0% or less. The sheet 2 in which the elongation of the reinforcement 10 is 15.0% or less is less likely to be deformed even when a tensile force is applied thereto. The sheet 2 has excellent handleability. From this point of view, the elongation of the reinforcement 10 is more preferably 13.0% or less and particularly preferably 11.0% or less. From the point of view of the compliance of the sheet 2, the elongation of the reinforcement 10 is preferably 5.0% or more, more preferably 7.0% or more and particularly preferably 8.5% or more.
[0057] The tensile strength and elongation were measured according to the test method for nonwovens defined in "JIS L 1913:2010". Test pieces for measurement were cut out from the reinforcement 10 or its original fabric. Five test pieces having a length direction consistent with the length direction of the reinforcement 10 or its original fabric and five test pieces having a length direction consistent with the width direction of the reinforcement 10 or its original fabric were used for measurement. Ten measured values were averaged, and the tensile strength and elongation were calculated.
[0058] In a plan view, the ratio of the area of the outline of the reinforcement 10 to the area of the sheet 2 used for the structure is preferably 60% or more. A reinforcement 10 in which this ratio is 60% or more can contribute to the operability of the sheet 2. From this point of view, the ratio is more preferably 70% or more and particularly preferably 75% or more. The ratio can be 100%. From the perspective of compliance at the seam 22, the ratio is preferably 95% or less.
[0059] [Fabric] Figure 7A reinforcement 10 is shown. In the reinforcement 10, a plurality of warp threads 26a and a plurality of weft threads 26b are woven. In other words, the reinforcement 10 is a woven fabric (cloth). In an embodiment of the present invention, the woven fabric has a planar woven structure. A woven fabric is a fabric. The reinforcement 10 (which is a fabric) can be impregnated with the composition of the intermediate layer 6. The impregnation can contribute to the large tensile strength of the sheet 2. The impregnation can further contribute to the small elongation of the sheet 2. The reinforcement 10 can be a fabric other than a woven fabric. As fabrics other than woven fabrics, knitted goods (knitted fabrics) and cross-point welded mesh fabrics are exemplified.
[0060] As materials for the reinforcement 10, synthetic resin compositions and metals are exemplified. As preferred base material resins for the synthetic resin composition, polyethylene terephthalate, polyethylene naphthalate, aramid, vinylon, polypropylene, polystyrene, and polyvinylidene fluoride are exemplified. As preferred metals, aluminum alloys, carbon steel, and alloy steel are exemplified. The use of the warp 26a and weft 26b having high tensile strength makes it possible to achieve a sufficiently high tensile strength of the sheet 2. The use of the warp 26a and weft 26b having a small elongation makes it possible to achieve a sufficiently small elongation of the sheet 2.
[0061] As from Figure 7 Clearly, the reinforcement 10 has a large number of meshes 28. In the embodiment of the present invention, the planar shape of each mesh 28 is generally square. The intermediate layer 6 penetrates these meshes 28. This penetration can contribute to the high tensile strength of the sheet 2. This penetration can further contribute to the small elongation of the sheet 2.
[0062] Figure 7 The arrow P1 in indicates the spacing of the yarns 26. The spacing P1 is preferably 1.0 mm or more and 50 mm or less. In the reinforcement 10 in which the spacing P1 is 1.0 mm or more, a large amount of polymer cement or the like penetrates the mesh 28. The reinforcement 10 can contribute to the high tensile strength and small elongation of the sheet 2. From this point of view, the spacing P1 is more preferably 1.2 mm or more and particularly preferably 1.5 mm or more. In the reinforcement 10 in which the spacing P1 is 50 mm or less, the reinforcement 10 can contribute to the high tensile strength and small elongation of the sheet 2. From this point of view, the spacing P1 is more preferably 40 mm or less and particularly preferably 35 mm or less.
[0063] Figure 7The arrow D1 in indicates the thickness of the yarn 26. The yarn 26 having a large thickness D1 makes it possible to achieve high tensile strength and small elongation of the sheet 2. From this point of view, the thickness D1 is preferably 0.05 mm or more, more preferably 0.10 mm or more, and particularly preferably 0.15 mm or more. The thickness is preferably 1.0 mm or less.
[0064] A non-woven reinforcement 10 may be included in the sheet 2 for a structure. As the non-woven reinforcement 10, non-woven fabrics, long fibers, resin films, and metal foils are exemplified. A large number of short fibers dispersed in the composition may be the reinforcement 10. The sheet 2 may also have a layer configuration in which the reinforcement 10 is not included.
[0065] [Extra Layer] The sheet material 2 for construction may have an additional layer located on the functional layer 4. A typical additional layer is a transparent paint layer. The additional layer may be a layer that reinforces or adds functions such as designability or thermal insulation properties. The sheet material 2 for construction may have a layer located between the functional layer 4 and the intermediate layer 6. The sheet material 2 for construction may have a layer located between the intermediate layer 6 and the adhesive layer 8.
[0066] [Total thickness] Figure 3 The arrow Tt in indicates the total thickness of the sheet 2. The total thickness Tt is preferably 200 μm or more, more preferably 400 μm or more and particularly preferably 500 μm or more. The total thickness Tt is preferably 5.0 mm or less, more preferably 3.0 mm or less and particularly preferably 1.0 mm or less. The distribution of the total thickness Tt is preferably within the range of ± 100 μm.
[0067] [Manufacturing method] Hereinafter, an example of a method for manufacturing the sheet 2 for a structure will be described. In the manufacturing method, a polymer composition for a functional layer 4 is mixed with a solvent, and a first coating is obtained. The first coating is applied to a base film, and a first coating film is obtained. The first coating film is heated, and the solvent is volatilized from the first coating. The base material polymer is cured by the heating, and the functional layer 4 is obtained.
[0068] Subsequently, the composite material for the intermediate layer 6 is mixed with a solvent, and a second paint is obtained. The second paint is applied to the functional layer 4, and a second coating film is obtained. The reinforcement 10 is pressed on the second coating film. The second coating film is heated, and the solvent is volatilized from the second paint. The polymer is cured by the heating, and the intermediate layer 6 including the reinforcement 10 is obtained.
[0069] Subsequently, the adhesive composition for adhesive layer 8 is mixed with a solvent to obtain a third coating. The third coating is applied to a release film to obtain a third coating film. The third coating film is heated to volatilize the solvent from the third coating to obtain an adhesive layer 8.
[0070] This adhesive layer 8 is overlapped with the intermediate layer 6. Furthermore, the base film is peeled from the functional layer 4, the release film is peeled from the adhesive layer 8, and the sheet 2 for a structure is obtained. The release film may remain in the sheet 2 for a structure.
[0071] [Effect] The sheet 2 for a structure has excellent conformability and can therefore be applied to a roof 12 in which there is a step 18 as described above. When a plurality of sheets 2 are repaired and pasted, the surface of the roof 12 can be covered with the sheet 2 in a wide area. Since the sheet 2 has the adhesive layer 8, it is not necessary to apply an adhesive to the roof 12. Since the adhesive layer 8 has excellent adhesion, even in the case where the material of the surface of the roof 12 is a composite material, the surface of the roof 12 can be covered with the sheet 2 in a wide area. For example, even in a roof 12 including both metal and artificial slate tiles on the surface, the surface of the roof 12 can be covered with the sheet 2 in a wide area.
[0072] The entire surface of the roof 12 may be covered with the sheet 2. In this specification, the surface of the roof 12 means a surface that can be visually identified when the roof 12 is viewed from above in the vertical direction. A repair method in which the entire surface of the roof 12 is covered with a single type of sheet 2 cannot be found from conventional construction methods.
[0073] The sheet 2 is lightweight compared to steel plates, copper plates, galvanized plates, etc. Therefore, even when the surface of the roof 12 is covered with the sheet 2 in a wide area, there is only a small adverse effect on the earthquake resistance of the building. From the viewpoint of earthquake resistance, the density of the sheet 2 is preferably 4.0 g / cm 3 or less, more preferably 3.0 g / cm 3 or less and particularly preferably 2.5 g / cm 3 This density is significantly lower than the density of an aluminum-zinc alloy coated steel plate (trade name "Galvalume steelplate") frequently used for repairing the roof 12 .
[0074] [Other uses] The sheet 2 can also help repair or reinforce structures other than the roof 12. Examples of structures other than the roof 12 include walls, pillars, eaves, fences, gates, doors, railings, copings, etc. of a house. The sheet 2 can also be used in commercial buildings, factories, warehouses, bridges, sewage facilities, railway facilities, utility poles, tunnels, etc.
[0075] [Repair and Reinforcement] After a structure (roof 12, etc.) is repaired or reinforced with the sheet 2 or a different sheet, there is a case where the sheet or structure breaks or deteriorates due to aging. Re-repair or re-reinforcement can be performed by pasting a newly prepared sheet 2 for the structure to the broken or deteriorated part of the sheet. When a new sheet 2 is pasted to an old sheet, the value of the structure can be maintained or maintained for an extremely long period of time. The pasting (overlapping) can be achieved with the adhesive force of the adhesive layer 8 in the new sheet 2. In this re-repair or re-reinforcement, there is no need to dispose of the old sheet. In this re-repair or re-reinforcement, waste generation can be suppressed. The sheet 2 conforms to the purpose of a circular economy. Even when a sheet 2 with a low density is laminated on an old sheet, there is only a small adverse effect on the earthquake resistance of the structure.
[0076] [Example 2] [Layer structure] Figure 8 FIG. 3 shows a sheet 30 for a structure according to another embodiment. The sheet 30 has a functional layer 32, an intermediate layer 34, and an adhesive layer 36. The specifications of the functional layer 32, the intermediate layer 34, and the adhesive layer 36, such as the material and the thickness, are similar to those of FIG. Figures 1 to 3 The functional layer 4, the intermediate layer 6 and the adhesive layer 8 of the sheet 2 for the structure shown in FIG. 3 are the same in specifications. The sheet 30 does not have a reinforcement 10 (refer to FIG. 3 ). Figure 3 ).
[0077] [Functional layer] The material of the functional layer 32 is Figures 1 to 3 The polymer composition for the functional layer 32 is the same as the polymer composition of the functional layer 4 shown in FIG. The polymer composition for the functional layer 32 contains a first base material polymer and a second base material polymer. The glass transition temperature of the second base material polymer (i.e., the second glass transition temperature T2) is lower than the glass transition temperature of the first base material polymer (i.e., the first glass transition temperature T1). The first base material polymer can contribute to the heat resistance of the sheet 30 for the structure. The second base material polymer can contribute to the compliance of the sheet 30 for the structure.
[0078] Examples Hereinafter, the effects of the sheet for a structure according to examples will be explained. The scope disclosed in the present specification should not be interpreted in a limited manner based on the description of these examples.
[0079] [Example 1] As the first base material polymer, an acrylic silicone resin having a glass transition temperature of 29.66°C was prepared. As the second base material polymer, an acrylic silicone resin having a glass transition temperature of -15.93°C was prepared. Seventy parts by mass of the first base material polymer and 30 parts by mass of the second base material polymer were mixed together with a defoaming adjustment mixer (trade name "AWATORI RENTARO AR-250" from THINKY CORPORATION), and a first coating was obtained. The mixing conditions are as described below: Stirring temperature: 25°C Stirring time: 2 min Speed: 2000 rpm Rotation speed: 800 rpm Defoaming time: 3 min Defoaming conditions: 2200 rpm and 60 rpm The first coating was applied to the release sheet with the relief shape using an applicator ("YBA-5 type" from Yoshimitsu Seiki, Japan) to obtain a first coating film. The first coating film was injected into an oven ("LC-114" from ESPEC CORP., Japan) and kept at a temperature of 80°C for one hour to produce a functional layer. The thickness of the functional layer was 110 μm. The elongation at break of the functional layer at -10°C, -5°C, 0°C, 5°C and 80°C measured by the above method (JIS K 7161) is shown in Table 1 below.
[0080] An acrylic emulsion (trade name "SPRING COAT BRUSH MIXTURE" described above) and a cement composition (trade name "SPRING COAT BRUSH POWDER" described above) are mixed together to obtain a second paint. The second paint is applied to the functional layer to obtain a second coating film. A woven fabric ("KANREISHA #600 CREMONA" from Kuraray Co., Ltd.) is pressed onto the second coating film as a reinforcement. The second coating film is heated to obtain an intermediate layer including the reinforcement. The thickness of the intermediate layer is 300 μm.
[0081] One hundred parts by mass of an adhesive containing an acrylic resin (the trade name "ORIBAIN BPS 6574" described above) and 6 parts by mass of an isocyanate-based curing agent (the trade name "BHS 8515" from TOYOCHEM CO., LTD.) were mixed together to obtain a third coating having a gel fraction of 57%. The third coating was applied to a release film to obtain a third coating film. The third coating film was heated to obtain an adhesive layer. The thickness of the adhesive layer was 100 μm.
[0082] The adhesive layer is overlapped with the intermediate layer. In addition, the release sheet is peeled off from the functional layer, and the release film is peeled off from the adhesive layer to obtain a Figures 1 to 3 A sheet for a structure of Example 1 of the layer configuration shown in FIG.
[0083] [Example 2 and Comparative Examples 1 to 3] Sheets for structures of Example 2 and Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the mass ratio between the first base material polymer and the second base material polymer was set as shown in Table 1 below.
[0084] [Heat resistance] The elongation at break of the functional layer in an environment of 80°C measured by the above method (JIS K 7161) is classified according to the following criteria: A: 400% or more B: 250% or more and less than 400% C: Less than 250% These results are shown in Table 1 below.
[0085] [Compliance] A worker was asked to perform work of attaching sheets for construction to a roof in a cold season. The worker was asked about compliance. Compliance was graded according to the following criteria: A: Extremely beneficial B: Favorable C: Poor These results are shown in Table 1 below.
[0086] [Table 1] .
[0087] As is clear from Table 1, the sheet for structures of each example was excellent in heat resistance and conformability. These evaluation results illustrate the superiority of the sheet for structures.
[0088] [Disclosed items] Each of the following items discloses a preferred embodiment.
[0089] [Project 1] A sheet material for a structure, comprising: an adhesive layer and a functional layer whose material is a polymer composition, wherein the polymer composition comprises a first base material polymer and a second base material polymer, The first base material polymer has a first glass transition temperature T1, The second base material polymer has a second glass transition temperature T2, and The second glass transition temperature T2 is lower than the first glass transition temperature T1.
[0090] [Project 2] The sheet for a structure according to item 1, wherein a difference (T1 - T2) between the first glass transition temperature T1 and the second glass transition temperature T2 is 30°C or more.
[0091] [Item 3] The sheet for structures according to item 1 or 2, wherein a mass ratio of the first base material polymer to the second base material polymer in the polymer composition is 30 / 70 or more and 80 / 20 or less.
[0092] [Item 4] The sheet for a structure according to any one of items 1 to 3, wherein the first glass transition temperature T1 is 25°C or higher.
[0093] [Item 5] The sheet for a structure according to any one of items 1 to 4, wherein the second glass transition temperature T2 is -10°C or lower.
[0094] [Item 6] The sheet for a structure according to item 4 or 5, wherein the first glass transition temperature T1 is 25°C or higher, and the second glass transition temperature T2 is -10°C or lower.
[0095] [Item 7] The sheet for a structure according to any one of items 1 to 6, wherein the polymer composition has an upper glass transition temperature TU and a lower glass transition temperature TL, The upper limit glass transition temperature TU is 30°C or lower, and the lower limit glass transition temperature TL is -15°C or higher.
[0096] [Item 8] The sheet for a structure according to any one of items 1 to 7, wherein the polymer composition contains a pigment, a filler or a reinforcing material.
[0097] [Item 9] The sheet for a structure according to any one of items 1 to 8, wherein the elongation at break of the functional layer is 10% or more and 175% or less in an environment at a temperature of 5°C.
[0098] [Item 10] The sheet for a structure according to any one of items 1 to 9, further comprising: an intermediate layer located between the functional layer and the adhesive layer, The material of the intermediate layer is a composite material containing a polymer and a filler (eg, cement).
[0099] [Item 11] The sheet for a structure according to any one of items 1 to 10, further comprising: a reinforcing material located between the functional layer and the adhesive layer, The reinforcement is a fabric.
[0100] [Item 12] A method for repairing or reinforcing a structure with a sheet material, the method comprising: (1) preparing a sheet comprising an adhesive layer and a functional layer whose material is a polymer composition, wherein the polymer composition comprises a first base material polymer and a second base material polymer, The first base material polymer has a first glass transition temperature T1, The second base material polymer has a second glass transition temperature T2, and The second glass transition temperature T2 is lower than the first glass transition temperature T1; and (2) The sheet is adhered to the surface of the structure using the adhesive force of the adhesive layer.
[0101] [Item 13] A method for re-repairing or re-reinforcing a structure repaired or reinforced with old sheets, the method comprising: (1) preparing a novel sheet material, the novel sheet material comprising an adhesive layer and a functional layer whose material is a polymer composition, wherein the polymer composition comprises a first base material polymer and a second base material polymer, The first base material polymer has a first glass transition temperature T1, The second base material polymer has a second glass transition temperature T2, and The second glass transition temperature T2 is lower than the first glass transition temperature T1; and (2) The new sheet is adhered to the broken or deteriorated surface of the old sheet using the adhesive force of the adhesive layer.
[0102] [Industrial Applicability] The sheet for a structure described above can be used in a state of being attached to various objects.
[0103] [reference numerals list] 2···Sheets for structures 2a···First sheet 2b···Second sheet 4. Functional layer 6···Middle Layer 8···Adhesive layer 10···Reinforcement 12···Roof 18···Step Difference 22···Seam 24···Step Difference 26···Yarn 26a···Meridian 26b···Weft 28···Grid 30···Sheets for structures 32···Functional layer 34···Middle layer.
Claims
1. A sheet material for a structure, comprising: Adhesive layer; as well as Its material is a functional layer of a polymer composition, wherein The polymer composition comprises a first base material polymer and a second base material polymer, The first base material polymer has a first glass transition temperature T1, The second base material polymer has a second glass transition temperature T2, and The second glass transition temperature T2 is lower than the first glass transition temperature T1.
2. The sheet material for a structure according to claim 1, wherein: A difference (T1 - T2) between the first glass transition temperature T1 and the second glass transition temperature T2 is 30° C. or more.
3. The sheet material for a structure according to claim 1 or 2, wherein: A mass ratio of the first base material polymer to the second base material polymer in the polymer composition is 30 / 70 or more and 80 / 20 or less.
4. The sheet material for a structure according to claim 1 or 2, wherein: The first glass transition temperature T1 is 25°C or higher.
5. The sheet material for a structure according to claim 1 or 2, wherein: The second glass transition temperature T2 is -10°C or lower.
6. The sheet material for a structure according to claim 1 or 2, wherein: The first glass transition temperature T1 is 25°C or higher, and the second glass transition temperature T2 is -10°C or lower.
7. The sheet material for a structure according to claim 1 or 2, wherein: The polymer composition has an upper glass transition temperature TU and a lower glass transition temperature TL, The upper limit glass transition temperature TU is 30°C or lower, and the lower limit glass transition temperature TL is -15°C or higher.
8. The sheet material for a structure according to claim 1 or 2, wherein: The polymer composition contains pigments, fillers or reinforcing materials.
9. The sheet material for a structure according to claim 1 or 2, wherein: The elongation at break of the functional layer is 10% or more and 175% or less in an environment at a temperature of 5°C.
10. The sheet material for a structure according to claim 1 or 2, further comprising: An intermediate layer located between the functional layer and the adhesive layer, wherein The material of the middle layer is a composite material containing a polymer and a filler.
11. The sheet material for a structure according to claim 1 or 2, further comprising: A reinforcement located between the functional layer and the adhesive layer, wherein The reinforcement is a fabric.
12. A method for repairing or reinforcing a structure using a sheet material, the method comprising: (1) preparing a sheet comprising an adhesive layer and a functional layer whose material is a polymer composition, wherein The polymer composition comprises a first base material polymer and a second base material polymer, The first base material polymer has a first glass transition temperature T1, The second base material polymer has a second glass transition temperature T2, and The second glass transition temperature T2 is lower than the first glass transition temperature T1; and (2) The sheet is adhered to the surface of the structure using the adhesive force of the adhesive layer.
13. A method for re-repairing or re-reinforcing a structure repaired or reinforced with old sheets, the method comprising: (1) preparing a novel sheet, the novel sheet comprising an adhesive layer and a functional layer whose material is a polymer composition, wherein The polymer composition comprises a first base material polymer and a second base material polymer, The first base material polymer has a first glass transition temperature T1, The second base material polymer has a second glass transition temperature T2, and The second glass transition temperature T2 is lower than the first glass transition temperature T1; and (2) The new sheet is adhered to the broken or deteriorated surface of the old sheet using the adhesive force of the adhesive layer.
Citation Information
Patent Citations
Structure protection sheet, execution method and precast member using structure protection sheet, and method for manufacturing precast member
WO2021010456A1